Integration of unified theory of acceptance and use of technology in internet banking adoption setting: Evidence from Pakistan. (August 2019) - Rahi, Samar; Abd.Ghani, Mazuri; Hafaz Ngah, Abdul
Abstract: The banking sector has evolved in information technology for their internal and external business operations. In effect, user acceptance of internet banking is considered as one of the most fundamental issue in banking sector. In order to identify which factors affect user intention to adopt internet banking, this study develops an amalgamated model based on technology and social psychological literature. The research model was empirically tested using 398 responses from customers of commercial banks. Data was analyzed using structural equation modeling (SEM). The results of this study provided theoretical and empirical support for newly developed integrated model. Importance performance matrix analysis (IPMA) revealed that assurance is the most influential factor among all others to determine user's intention to adopt internet banking. These findings provide valuable insight to marketers and managers to understand customer behavior towards adoption of technology, especially in emerging e-payment domain. To the best of our knowledge, this is the first study that investigates internet banking adoption issues with integrated technology model (UTAUT & E-SQ) in South Asia. Finally the study calls for researchers to use current integrated model in other e-commerce domains such as online shopping websites to establish the external validity of the model. Graphical abstract: Image 1 Highlights: This study develops a new integrated technology adoption model to investigate user intention to adopt internet banking. This study reveals the impact of performance expectancy, effort expectancy, social influence and facilitating condition on user intention to adopt internet banking. It inspects the effect of customer service, website design, assurance, and reliability on user intention to adopt internet banking. The study highlights managerial implications using Importance performance matrix analysis (IPMA).